Influence of Psychological Separation on Master Graduates’ Career Maturity: Mediating Role of Occupational Self-Efficacy - Jianchao, Ni; Yumei, Wang; Dongchen, Li (Frontiers in Psychology, 2022)
This research adopts the career maturity as an indicator of one’s intention and ability in career development, and explores whether and how psychological separation from parents and occupational self-efficacy influence one’s career maturity. A structural equation model is constructed and tested with data from a survey of 584 master graduates in top universities across China. According to the study, it is founded that: (1) The psychological separation and occupational self-efficacy of master graduates are significantly and positively correlated with occupational self-efficacy, and career maturity, respectively. (2) Occupational self-efficacy plays a part of the mediating role between psychological separation and career maturity. (3) Master graduates with a high degree of psychological separation are more confident in achieving their career goals, more involved in the career selection process and have a higher level of career development. These findings will arouse the attention of the society to the master graduates’ career maturity to some extent.